Multifocal Tuberculosis with Pre-Extensive Drug Resistance (Clinical Case) - Raznatovska, O. M.; Petrenko, V. I.; Shalmin, O. S.; Yasinskyi, R. M.; Fedorets, A. V.; Svitlytska, O. A.; Разнатовська, Олена Миколаївна; Петренко, В. І.; Шальмін, Олександр Самуілович; Ясінський, Роман Миколайович; Федорець, Андрій Васильович; Світлицька, Оксана Анатоліївна (My University, 2023)
We present our own observation of the multifocal tuberculosis with pre-extensive drug resistance (pre- XDR-TB) development in a patient who was treated in the pulmonary tuberculosis department No. 2 of the Zaporizh zhia’ regional phthisio-pulmonology clinical treatment and diagnostic center. Multifocal pre-XDR-TB developed in the patient 2.5 months after the initial diagnosis of destructive disseminated pulmonary tuberculosis. The patient was treated during 2 months with deforming arthrosis, which turned out to be tuberculosis of the left knee joint until the specified changes in the lungs were detected, which indicates its late diagnosis. The patient was not tested for HIV infection when tuberculosis was detected in the primary care, and after 2.5 months it was firstly found and accompanied by severe immunosuppression (CD4 lymphocytes count was 94 cells). This fact also indicates a late diagnosis of HIV infection. As a result of untimely diagnosis and treatment of disseminated pulmonary tuberculosis in the pre-XDR-TB patient with combined HIV infection, there was a rapid generalization of a specific process with the development of multifocal tuberculosis involving not only the bronchopulmonary system, but also the left eye (focal chorioretinitis), the heart (exudative pericarditis), brain (meningoencephalitis) and the left knee joint. The presented clinical case also shows the irresponsibility of the patient to his healthy and the poor work of the family doctor in explaining to the patient the importance of timely tuberculosis treatment. Thus, in the described clinical case, a latediagnosed HIV infection with severe immunosuppression may have been the trigger for the development of multifocal tuberculosis with extensive drug resistance in the patient and untimely treatment of disseminated pulmonary tuberculosis led to rapid generalization of the specific process. More responsible work of family doctors with tuberculosis patients is also necessary. Therefore, timely diagnosis of multifocal tuberculosis and the earliest appointment of antimycobacterial therapy will allow not only to achieve positive results in treatment, but also to prevent the complications’ development. Представлено власне спостереження розвитку мультифокального туберкульозу з пре-широкою лікарською стійкістю (пре-ШЛС-ТБ) у пацієнта віком 46 років, який перебував на лікуванні у відділенні легеневого туберкульозу № 2 Запорізького регіонального фтизіопульмонологічного клінічного лікувально-діагностичного центру. У пацієнта за 2,5 міс від початкової діагностики деструктивного дисемінованого туберкульозу легень розвинувся мультифокальний пре-ШЛС-ТБ. До виявлення зазначених змін у легенях пацієнт 2 міс лікував артроз, що деформує, який виявився туберкульозом лівого колінного суглоба, що вказує на пізню його діагностику. Під час виявлення туберкульозу на первинній ланці пацієнту не проводили тесту на ВІЛ-інфекцію. Через 2,5 міс виявлено її наявність. ВІЛ-інфекція супроводжувалася тяжкою імуносупресією (CD4-лімфоцити – 94 клітини). Це також свідчить про пізню діагностику ВІЛ-інфекції. Через несвоєчасну діагностику та лікування дисемінованого туберкульозу легень у пацієнта з пре-ШЛС-ТБ на тлі ВІЛ-інфекції розвинувся мультифокальний туберкульоз із залученням у процес не лише бронхолегеневої системи, а і лівого ока (вогнищевий хоріоретиніт), серця (ексудативний перикардит), головного мозку (менінгоенцефаліт), лівого колінного суглоба. Представлений клінічний випадок також свідчить про безвідповідальне ставлення пацієнта до здоров’я та погану роботу сімейного лікаря щодо пояснення пацієнту актуальності вчасного виявлення та лікування туберкульозу. В описаному клінічному випадку пусковим механізмом розвитку мультифокального туберкульозу з пре-ШЛС-ТБ у пацієнта, можливо, стала недіагностована вчасно ВІЛ-інфекція з тяжкою імуносупресією. Є потреба у відповідальнішій роботі сімейних лікарів із хворими на туберкульоз. Вчасна діагностика мультифокального туберкульозу з якомога ранішим призначенням антимікобактеріальної терапії дасть змогу не лише досягти позитивних результатів лікування, а і запобігти розвитку ускладнень.
Мультифокальний туберкульоз з пре-широкою лікарською стійкістю (клінічний випадок)
Keywords: Multifocal tuberculosis; pre-extensive drug resistant tuberculosis; мультифокальний туберкульоз; туберкульоз із множинною лікарською стійкістю